Robustness Report on "Discretionary Tax Changes and the Macroeconomy: New Narrative Evidence from the United Kingdom", by James Cloyne (2013) - Joseph Kopecky; Douglas Campbell; Abel Brodeur; Magnus Johannesson; Lester Lusher; Nikita Tsoy (Institute for Replication (I4R), 2024)
Cloyne (2013) constructs a novel dataset documenting fiscal tax shocks in the United Kingdom using the narrative approach developed by Romer and Romer (2010), and estimates the impact of tax changes on GDP. He finds that a tax cut of one percent of GDP causes a 0.6 percent increase in output in the initial quarter of the policy, rising to a peak of 2.5 percent over three years. We first reproduce all of the VAR tables and figures in the original paper, and then test for robustness through a number of changes to the baseline regression model, particularly: changes in lag structure, changes in the control set, alternative estimation procedures, and excluding influential observations. In 60% of robustness the impact effect is significant at the 95% level, with a mean estimated coefficient of 0.63, while in 70% of robustness tests the peak response remains significant at the 95% level, with a mean peak response of 2.27.
Keywords: E23; E32; E62; H20; H61; 330; Fiscal policy; taxation; narrative shocks; macroeconomics